High Risk Factors of The Balikpapan RU-V RDMP Mega Project on Project Success - Ambarwaty Syahdiana Umar; Surya Raharja (Yayasan Riset dan Pengembangan Intelektual, 2024)
A project's ability to manage risks and overcome challenges that arise during implementation can play a large role in determining its success. Project success can also be measured through the level of innovation implemented and operational efficiency achieved. This research aims to examine how natural risks, design risks, resource risks, financial risks, and legal and regulatory risks influence project success. The problem in this research is project quality problems which can result in delays in project implementation. The analysis method uses quantitative with multiple regression analysis techniques. Population of all employees on the Balikpapan RDMP Project. The sample was determined using purposive sampling, namely Leaders, Managers and Field Staff, totaling 66 employees. The research results show that the natural risk p-value is 0,000, resource risk p-value 0,044, and financial risk p-value 0.048 which means influentialsignificant negative impact on the success of the RU-V RDMP Balikpapan mega project, while the design risk p-value is 0,994and regulatory legal risk, the p-value of 0.674 has no effect on the success of mega projects.